2017
DOI: 10.3389/fnut.2017.00030
|View full text |Cite
|
Sign up to set email alerts
|

Risk–Benefit Assessment of Monomethylmercury and Omega-3 Fatty Acid Intake for Ringed Seal Consumption with Particular Emphasis on Vulnerable Populations in the Western Canadian Arctic

Abstract: Many northern Inuit communities rely on traditional food as major source of nourishment. An essential part of the traditional Arctic diet is marine mammals such as ringed seals or beluga. Being top predators, these animals are often highly contaminated with various toxins. In contrast, some tissues of marine mammals are also characterized by high amounts of n3-PUFAs (omega-3 polyunsaturated fatty acids). Here, we try to balance the risks associated with the consumption of different tissue types of ringed seals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Consequently, according to Bayesian mixing models based on Hg isotope tracers, the NES contribution to MeHg levels in shark muscle was estimated to be 25% maximum (Figure B). Lipid reserves represent major sources of metabolic energy in marine predators that have very high energetic requirements related to long migrations. , To cover energy needs related to undertaking long migrations, white sharks are hypothesized to rely primarily on the blubber of marine mammals during the inshore season. ,, Indeed, fat can exceed 40% of the total body mass in juvenile NES, which are believed to be a preferred prey for white sharks due to their high energy supply. , As MeHg primarily binds to thiol-containing amino acids in proteins, blubber which is mainly composed of lipids generally contains low MeHg levels in seals . Thus, despite a presumed high feeding rate during the inshore season, low MeHg levels in pinniped blubber may be responsible for the limited contribution of NES to the global MeHg exposure for white sharks (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, according to Bayesian mixing models based on Hg isotope tracers, the NES contribution to MeHg levels in shark muscle was estimated to be 25% maximum (Figure B). Lipid reserves represent major sources of metabolic energy in marine predators that have very high energetic requirements related to long migrations. , To cover energy needs related to undertaking long migrations, white sharks are hypothesized to rely primarily on the blubber of marine mammals during the inshore season. ,, Indeed, fat can exceed 40% of the total body mass in juvenile NES, which are believed to be a preferred prey for white sharks due to their high energy supply. , As MeHg primarily binds to thiol-containing amino acids in proteins, blubber which is mainly composed of lipids generally contains low MeHg levels in seals . Thus, despite a presumed high feeding rate during the inshore season, low MeHg levels in pinniped blubber may be responsible for the limited contribution of NES to the global MeHg exposure for white sharks (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…Past research has focused on defining food insecurity, assessing its prevalence and examining the key factors that lead to such high rates amongst Inuit in Nunavut. Factors impacting food insecurity in previous research include the nutrition transition away from country food due to contaminant concerns, increasing consumption of market foods with increasing availability in stores alongside decreasing access to country food, changes in family composition and rising costs of gas and hunting equipment; some research has investigated the potential for a country food market to address some of these concerns (Thompson 2005;Chan et al 2006;Donaldson et al 2010;Ford et al 2010;Berrang-Ford et al 2011;Council of Canadian Academies 2014;Guo et al 2015;Ford et al 2016;Ready 2016Ready , 2018aSearles 2016;Gmelch et al 2017). "Country food" is the term Inuit use for foods harvested locally, such as caribou, seal, berries and eggs.…”
Section: Introductionmentioning
confidence: 99%
“…A nascent body of research uses mathematical modelling to investigate the trade-offs of CF and MF based on food availability, cultural appropriateness, nutrition and health outcomes, and economic feasibility (17) . Such techniques have informed specific recommendations for food substitutions using food replacement modelling (17,45,57,206,207) . For example, Calder and colleagues suggested that replacing CF with locally caught Atlantic salmon will lead to net benefits for neurodevelopmental and cardiovascular health and reduced risk of cancer in three communities in Nunatsiavut (45) .…”
Section: Discussionmentioning
confidence: 99%
“…environmental contaminants) and outcomes (e.g. physical health) (207,208) . No studies have attempted to conduct actionable risk-benefit analyses of the trade-offs between traditional food and MF consumption that simultaneously incorporate multiple dimensions of health (e.g.…”
Section: Box 2: Gaps In Research On Drivers and Implications Of The Dietary Transition Among Inuitmentioning
confidence: 99%